Drug-Induced Sleep Computed Tomography–Directed Upper Airway Surgery for Obstructive Sleep Apnea: A Pilot Study. (January 2019) - Lee, Li-Ang; Wang, Chao-Jan; Lo, Yu-Lun; Huang, Chung-Guei; Kuo, I-Chun; Lin, Wan-Ni; Hsin, Li-Jen; Fang, Tuan-Jen; Li, Hsueh-Yu
Objective: A surgical response to upper airway (UA) surgery for obstructive sleep apnea (OSA) depends on adequate correction of collapsible sites in the UA. This pilot study aimed to examine the surgical response to UA surgery directed by drug-induced sleep computed tomography (DI-SCT) for OSA. Study Design: Prospective case series. Setting: Tertiary referral center. Subjects and Methods: This study recruited 29 OSA patients (median age, 41 years; median body mass index, 26.9 kg/m 2 ) who underwent single-stage DI-SCT-directed UA surgery between October 2012 and September 2014. DI-SCT was performed with propofol for light sedation with a bispectral monitor before and after UA surgery. Nonresponders were defined as those with a reduction in apnea-hypopnea index <50% after 6 months following UA surgery. Results: DI-SCT showed that 28 (97%) patients had collapses at multiple sites, all of whom underwent multilevel UA surgery accordingly. The apnea-hypopnea index decreased from 53.6 to 26.8 ( P < .001). There were 18 (62%) nonresponders and 11 (38%) responders. Multiple-site collapses could not predict surgical response ( P > .99). The nonresponders had significant improvements in velopharyngeal, oropharyngeal lateral wall, and tongue collapses (all P < .05), whereas the responders had significant improvements in velopharyngeal and oropharyngeal lateral wall collapses (both P ≤ .05). Conclusion: Despite multilevel OSA surgery, residual UA obstruction in nonresponders likely occurs due to multiple mechanisms. DI-SCT may help to elucidate the reasons for a nonresponse.